Laparoscopic and Open Distal Pancreatectomy—An Initial Single-Institution Experience with a Propensity Score Matching Analysis - Irena Plahuta; Žan Šarenac; Medeja Golob; Špela Turk; Bojan Ilijevec; Tomislav Magdalenić; Stojan Potrč; Arpad Ivanecz (Life)
Laparoscopic distal pancreatectomy is a minimally invasive approach for the surgical treatment of neoplasms in the distal pancreas. This study aimed to compare this approach to the open procedure. A retrospective analysis of a prospectively maintained database of 400 pancreatectomies was performed. The laparoscopic distal pancreatectomy group (LDP) was compared to the open distal pancreatectomy group (ODP). A propensity score matching analysis (PSM) was performed. From 2016 to 2023, 108 distal pancreatectomies were carried out, 19 (17.6%) laparoscopically and 89 (82.4%) openly. The conversion rate was 13.6%. The severe morbidity rates were 28.1% in the ODP group, 47.4% in the LDP group, and 15.8% in the ODP-PSM group. The difference between the latter two was statistically significant (p = 0.034) due to the high rate of Clavien–Dindo grade 3a complications (42.1% versus 10.5%, p = 0.042) in the LDP group. The 90-day mortality rates were 3.3% in the ODP group and 5.3% in the other two groups. The LDP group had a shorter duration of intravenous narcotic analgesia (5 versus 7 days, p = 0.041). There was no difference in the R0 resection or postoperative pancreatic fistula rates. Our attention should be drawn to preventing postoperative complications because the oncological outcomes are already comparable with those of the open procedure, and postoperative pain management is promising.